2009
DOI: 10.1590/s0004-282x2009000600016
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the use of MIG3 bioceramics fabrics use - long infrared emitter - in pain, intolerance to cold and periodic limb movements in post-polio syndrome

Abstract: -The main post-polio syndrome (PPS) symptoms are new-onset weakness, new-onset atrophy, fatigue, cold intolerance, and pain associated with sleep disturbances. The polysomnographic study is the gold pattern to analyze sleep disorders. Objective: To assess pain, intolerance to cold and periodic limb movements (PLM) index before and after the use of MIG3 bioceramic fabrics over 4 weeks. Method: 12 patients with PPS from UNIFESP/EPM. All patients were submitted to polysomnography and infra-red examinations with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 10 publications
1
13
0
2
Order By: Relevance
“…Adaptive equipment, such as raised toilets, grab bars, stair glides, modified utensils, and home modifications, may also be recommended. A preliminary study evaluating the use of bioceramic fabrics in clothes and mattresses in patients with PPS noted a decrease in pain and periodic limb movements . Bioceramics are inorganic, non‐metallic, polycrystalline compounds that emit far‐infrared radiation that has been found to have a number of health benefits, including analgesic, anti‐inflammatory, and antioxidative properties .…”
Section: Treatment and Managementmentioning
confidence: 99%
“…Adaptive equipment, such as raised toilets, grab bars, stair glides, modified utensils, and home modifications, may also be recommended. A preliminary study evaluating the use of bioceramic fabrics in clothes and mattresses in patients with PPS noted a decrease in pain and periodic limb movements . Bioceramics are inorganic, non‐metallic, polycrystalline compounds that emit far‐infrared radiation that has been found to have a number of health benefits, including analgesic, anti‐inflammatory, and antioxidative properties .…”
Section: Treatment and Managementmentioning
confidence: 99%
“…The use of transcutaneous electric nerve stimulation (TENS) and acupuncture may also contribute to effective treatment to strengthen weakened muscles as well as to decrease pain (Gevirtz, 2006; Shi, 1996). In a controlled clinical trial, the use of a long‐term infrared emitter from bioceramic tissue over 4 weeks showed a significant reduction in pain intensity (8.3 ± 2.5 vs. 3.8 ± 2.5) and an improvement in sleep quality measured by polysomnographic examination that demonstrated a significant decrease in the PLM index (11 ± 14 vs. 3.7 ± 6.3) in 12 patient with cold intolerance and restless legs syndrome (Silva et al, 2009). A case report showed a positive result of Cannabis sativa oil to control nausea and abdominal pain as somatoform autonomic function disorder of the upper gastrointestinal tract of a eldery SPP patient, becoming a possible pharmacological option for some patients with functional disorders resistant to antiemetic and pain‐modulating drugs (Bleckwenn, Weckbecker, & Voss, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The intensities of infrared (IR) light emitted by ceramic devices exposed to human body temperatures are much smaller than those emitted by electrically heated plates and other sources, raising some doubt that the IR ceramic emission is solely responsible for the observed biological effects. Despite the unclear mechanism of action, the modulation of biological parameters by the devices, creams and clothing containing those inorganic particulates has been demonstrated, encouraging further investigation on the subject.…”
Section: Introductionmentioning
confidence: 99%
“…Significant improvements in pathological conditions, such as pain, blood dyscrasias, and cellulite, have been reported for individuals wearing accessories containing ceramics. A more recent work reported reductions in body measurements after 30 days of daily use of high‐waist undershorts made of synthetic fabrics with embedded ceramic particles.…”
Section: Introductionmentioning
confidence: 99%